A comparison of intravenous and intradiscal delivery of multipotential stem cells on the healing of injured intervertebral disk. Issue 6 (27th February 2014) - Tam, Vivian; Rogers, Ian; Chan, Danny; Leung, Victor Y. L.; Cheung, Kenneth M. C.
ABSTRACT A major hurdle of cellular therapy for biological treatment of intervertebral disk (IVD) degeneration is the delivery method where current delivery methods are limited to intradiscal injection which can potentially cause further degeneration. Recent studies indicated that multipotential stem cells (MPSCs) from human umbilical cord blood home to injured sites and induce local therapeutic changes, thereby potentially addressing the drawbacks of direct delivery. We tested the effects of these cells on injured IVD using a mouse model of puncture‐induced degeneration via two delivery methods. Caudal IVD underwent needle puncture, and MPSCs were injected indirectly (intravenously), or directly (intradiscally) into the nucleus pulposus. IVD were harvested for histological, gene and protein analysis after 14 weeks. Our finding showed limited homing ability of the MPSCs. However, regardless of delivery method, no engraftment or expansion of MPSCs was observed at the injured site. Contrasting to direct injection, intravenous injection neither improved the degeneration status, nor preserve disk height, however, both delivery methods increased glycosaminoglycan (GAG) protein and Acan gene expression relative to controls, suggesting possible paracrine effects. Identifying the mechanisms by which MPSCs act on endogenous IVD cells would provide insights into the potential of these cells to treat IVD injuries and degeneration. © 2014 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 32:819–825, 2014.